PENGARUH PERENCANAAN PEMBELAJARAN TERHADAP PENINGKATAN KUALITAS MENGAJAR GURU DI SD NEGERI 060938 MEDAN JOHOR - Srie Faizah Lisnasari (PGSD Universitas Negeri Medan, 2018)
This study aims to determine the application of Teacher learning plan in SD Negeri 060938 Medan Johor, to know the quality of teaching teachers and to know the effect of lesson planning on improving the quality of teaching Teachers at SD Negeri 060938 Medan Johor. The study population is all teachers in SD Negeri 060938 Medan Johor which amounts to 23 people. The results of this study illustrates that the professionalism of teachers SD Negeri 060938 Medan Johor in teaching is quite good and has achieved the goal of learning as expected, as the results showed that 49.60% success is supported by teachers who have quality competencies and master the material quality curriculum is also reflected in the evaluation results of the semester exam the value of its objectivity is in the category on very well. Keywords: Learning Planning, Teaching Quality, Elementary School Teachers.